The relationship between logical mathematical intelligence and learning independence on mathematics learning outcomes - RM, Bambang; Umam, Khairul; suhartati, suhartai; Yuhasriati, Yuhasriati; Shelvia, Oktayana (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
Logical mathematical intelligence and learning independence are two important aspects that can be crucial for students' learning success. This study aims to: (1) determine the relationship between logical mathematical intelligence and students' mathematics learning outcomes; (2) determine the relationship between learning independence and students' mathematics learning outcomes; (3) determine the relationship between logical mathematical intelligence and learning independence together with students' mathematics learning outcomes. This research uses a quantitative approach with a correlational research type. The population of this study were all X1 classes in SMA Negeri 4 Banda Aceh. The sample in this study were students of class XI-EB2, which were selected using simple random sampling technique. Data collection was conducted using questionnaires and tests. The data analysis technique uses simple correlation analysis, multiple correlation, t-test and F-test after the test conditions are met. The results showed that: (1) logical mathematical intelligence with students' mathematics learning outcomes has a positive and significant relationship of 30.04%; (2) learning independence with students' mathematics learning outcomes has a positive and significant relationship of 29.99%; and (3) logical mathematical intelligence and learning independence together have a positive and significant relationship with students' mathematics learning outcomes of 26.5%.